Impact of different concurrent training sequencing schemes on overnight systemic immunological regulation in adolescent athletes - Thomas Steidten; Urs Granacher; Holger Gabriel; Simon Haunhorst; Simon Haunhorst; Philipp Reuken; Diana Dudziak; Christian Puta; Christian Puta; Christian Puta (Frontiers in Physiology)
Physical exercise can have acute or short-term effects on immunological overnight recovery. Concurrent training (CT) is an often-applied exercise regime in team (e.g., soccer) and individual sports (e.g., judo, rowing) characterized by high training volumes and/or intensities. CT can be programmed in different sequencing schemes including strength/power before endurance training or vice versa. Here, we aimed to examine the acute effects (one exercise session) of different CT sequencing schemes on immunological recovery in young athletes. Male judo athletes (Tier 3, highly trained, national level) aged 16.0 ± 1.8 years were recruited to participate in a crossover repeated measures study design. Participants performed a power-endurance and an endurance-power CT sequence on separate days. Immunological stress regulation using capillary blood markers were tested immediately after the CT session and the night before (baseline) and after (intervention) CT sessions. Baseline evening measurements were performed from 5:00 p.m. to 7:00 p.m. and intervention evening measurements 6 h after the CT. Capillary blood markers were taken from the earlobe, plasma volume corrected, referenced to baseline and analyzed for order-by-time interactions using a generalized estimating equations statistical approach. White blood cells (p < 0.05), granulocytes (p < 0.001), the systemic inflammation index (p < 0.05), and the systemic inflammation response index (p < 0.001) showed significant group-by-time interactions. In contrast, monocytes, lymphocytes, and platelets did not exhibit a significant group-by-time effect (p > 0.05). Results were adjusted for repeated measurements using Bonferroni-Holm correction, which showed a significantly (p < 0.001) stronger immunological overnight regulation for granulocytes and the systemic inflammation response index following the power-endurance sequencing scheme, whereas white blood cells, lymphocytes, monocytes, blood platelets, and the systemic inflammation index did not show significant group-by-time interactions (p > 0.05). The observed findings for granulocytes and the systemic inflammation response index might be related to altered systemic stress regulation after the training session as the power-endurance sequence showed a higher increase in granulocytes on the evening after the exercise. Sleep behavior could affect the immunological systemic recovery and should therefore be further studied in future research. If immunological stress is already present, the endurance-power sequencing scheme appears to be more appropriate.